English in speech and writing : investigating language and literature - Hughes, Rebecca, 1962- (Routledge, 1996)
In this activity-based text, Rebecca Hughes invites the reader to examine the differences between spoken and written English. Instead of presenting a bewildering array of 'facts' about variety in English, she encourages the reader to actively investigate the differences between these two modes of communication by comparing actual speech patterns with literary ones. This indispensable guide to the basic methods of analysis provides both an overview of the relationship between speech and writing and an introduction to a central theoretical issue in language studies. By the end of the book, readers will have had the opportunity to consider material from an extensive selection of spoken and written varieties - including boxing commentaries, detective novels and film scripts - while being encouraged to formulate their own opinions with regard to lexis and structure. In addition, the tasks that have been incorporated into the end of every chapter provide suggestions for further self-study and follow-up work.- Resumé vydavatel
Keywords: angličtina; diskurzivní analýza; mluvený projev; syntax; psaný projev; English language; spoken language; discourse analysis; written language; elektronické knihy; monografie; electronic books; monographs